2016
DOI: 10.1088/0264-9381/33/4/045004
|View full text |Cite
|
Sign up to set email alerts
|

Does Newton’s gravitational constant vary sinusoidally with time? Orbital motions say no

Abstract: A sinusoidally time-varying pattern of the values of the Newton's constant of gravitation G measured in Earth-based laboratories over the latest decades has been recently reported in the literature. We put to the test the hypothesis that the aforementioned harmonic variation may pertain G itself in a direct and independent way. We numerically integrated the ad-hoc modified equations of motion of the major bodies of the Solar System by finding that the orbits of the planets would be altered by an unacceptably l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…A non-constant G would have serious implications both for Newtonian physics and for General Relativity. This motivates ongoing efforts to devise new methods to measure this quantity, and to push the limits of experimental accuracy in order to test the constancy of G [358][359][360][361][362].…”
Section: Cosmological Testsmentioning
confidence: 99%
“…A non-constant G would have serious implications both for Newtonian physics and for General Relativity. This motivates ongoing efforts to devise new methods to measure this quantity, and to push the limits of experimental accuracy in order to test the constancy of G [358][359][360][361][362].…”
Section: Cosmological Testsmentioning
confidence: 99%
“…Note that tighter constraints on oscillations in G can be derived from the orbits of the planets in the Solar System when ν ∼ yr −1 [30].…”
Section: Observational Constraintsmentioning
confidence: 99%
“…Besides, after enlarging the Glab data base and a few corrections to the time interval the measurements were carried out, Schlamminger et al concluded that this significantly weakens the correlation to the LOD [8]. Besides, based on the aforementioned hypothesis, L. Iorio could predict for the LAGEOS satellite an orbital increase as large as 3.9 m yr −1 in contrast with the observed decay of − 0.203 ± 0.035 m yr −1 and an anomalous perihelion precession as large as 14 arcseconds per century for Saturn [9]. Moreover, these claims have been disputed by other authors [10,11,12].…”
Section: I-introductionmentioning
confidence: 98%